Effect of Ultrasonic Processing on Mechanical and Surface Properties of Chitosan-Alginate-Starch Edible Films - Desi Rahmawati; Azafilmi Hakiim; Indah Cintami; Alehandro Sitinjak (Universitas Negeri Semarang, 2025)
Marine plastic waste has driven the development of biodegradable packaging alternatives such as edible films. However, their mechanical strength and structural homogeneity remain challenging. This study investigates the effect of ultrasonic processing on the mechanical and surface properties of edible films based on chitosan–alginate–starch blends. Edible films were prepared with various polysaccharide combinations and subjected to ultrasonic treatment during processing. The sample was treated with ultrasonic waves at a frequency of 37 kHz and a temperature of 30 °C for 3 minutes. The results show that ultrasonic treatment improved surface homogeneity, as indicated by smoother structures and reduced bubble formation compared to non-ultrasonic films. In terms of mechanical properties, ultrasonic treatment exhibited varying effects on tensile strength but consistently increased elongation at break, indicating enhanced flexibility. The highest tensile strength was observed in chitosan-based films (45.479 MPa), while the highest elongation (41%) was achieved in chitosan–alginate films under ultrasonic treatment. The ternary blend (chitosan–alginate–starch) demonstrated balanced mechanical properties in both ultrasonic and non-ultrasonic conditions. Chemical analysis using FTIR spectroscopy showed that ultrasonic treatment affected intermolecular interactions within the film matrix, as indicated by shifts and changes in the intensity of absorption bands in several functional groups. These findings suggest that ultrasonic processing plays a crucial role in improving film structure and flexibility, while the polysaccharide composition governs the balance between strength and elasticity.